Carbon pricing under binding political constraints - Jesse D. Jenkins; Valerie J. Karplus (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
The economic prescription for climate change is clear: price carbon dioxide (CO2) and other greenhouse gas emissions to internalize climate damages. In practice, a variety of political economy constraints prevent the introduction of a carbon price equal to the full social cost of emissions. This paper develops insights about the design of climate policy in the face of binding political constraints, formulated here as limits on the CO2 price itself, on increases in energy prices, and on energy consumer and producer surplus loss. We employ a stylized model of the energy sector to develop intuition about the welfare-maximizing combination of CO2 price, subsidy for clean energy production, and lump-sum transfers to energy consumers or producers under each constraint. We find that the strategic use of subsidies or transfers can compensate for or relieve political constraints and significantly improve the efficiency and environmental efficacy of carbon pricing policies.
Keywords: H23; Q48; Q54; Q58; 330; political economy; carbon pricing; environmental economics; public economics; climate change; instrument choice; carbon tax; emissions trading